The Effects of Bilateral and Ipsilateral Auditory Stimuli on the Subcomponents of Visual Attention. (November 2021) - Fu, Jing; Guo, Xuanru; Tang, Xiaoyu; Wang, Aijun; Zhang, Ming; Gao, Yulin; Seno, Takeharu
Attention contains three functional network subcomponents of alerting, orienting, and executive control. The attention network test (ANT) is usually used to measure the efficiency of three attention subcomponents. Previous researches have focused on examining the unimodal attention with visual or auditory ANT paradigms. However, it is still unclear how an auditory stimulus influences the visual attention networks. This study investigated the effects of bilateral auditory stimuli (Experiment 1) and ipsilateral auditory stimulus (Experiment 2) on the visual attention subcomponents. We employed an ANT paradigm and manipulated the target modality types, including visual and audiovisual modalities. The participants were instructed to distinguish the direction of the central arrow surrounded by distractor arrows. In Experiment 1, we found that the simultaneous bilateral auditory stimuli reduced the efficiency of visual alerting and orienting, but had no significant effect on the efficiency of visual executive control. In Experiment 2, the ipsilateral auditory stimulus reduced the efficiency of visual executive control, but had no significant effect on the efficiency of visual alerting and orienting. We also observed a reduced relative multisensory response enhancement (rMRE) effect in cue condition relative to no cue condition (Experiment 1), and an increased rMRE effect in congruent condition compared with incongruent condition (Experiment 2). These results firstly provide evidence for the alerting, orienting and executive control effects in audiovisual condition. And the bilateral and ipsilateral auditory stimuli have different effects on the subcomponents of visual attention.